PENGEMBANGAN MODUL BERBASIS REALISTIC MATHEMATICS EDUCATION (RME) TERINTEGRASI PROFIL PELAJAR PANCASILA PADA MATERI BANGUN DATAR UNTUK SISWA SEKOLAH DASAR - Neny Kennesthy Anggraeni; Muflikhul Khaq; Rintis Rizkia Pangestika (Jurnal Binagogik, 2024)
This research aims to: 1) Produce a Module product based on Realistic Mathematics Education (RME) Integrated with Pancasila Student Profiles in Flat Building Material for Elementary School Students in accordance with development procedures, 2) Determine the feasibility of a Module Based on Realistic Mathematics Education (RME) Integrated with Pancasila Student Profiles .The type of research used in the research is research and development (Research and Development) using the Borg and Gall model which consists of 10 stages. The research subjects were fourth grade students at SD Negeri 1 Baledono for the 2022/2023 academic year with a total of 28 students. Data collection techniques in this research used observation, interviews and questionnaires. The data obtained is product validation and student response questionnaires. Data analysis by calculating validity using a predetermined equation, then the results are converted into grades and converted to a scale of 4 for validation while student responses are on a scale of 1. Results of research on the development of an Integrated Realistic Mathematics Education (RME) Module Based on Student Profiles Pancasila in Flat-Round Material is: 1) producing a product in the form of an Integrated Realistic Mathematics Education (RME) Based Module Student Profile Pancasila in Flat-Round Material for Elementary School Students, 2) The product validity results obtained an average score of 3.59 in the very valid category, 3) Practicality results obtained an average score of 83% in the very practical category. Based on this study, it can be concluded that the Integrated Realistic Mathematics Education (RME) Based Module on Pancasila Student Profiles in Flat Building Material for Elementary School Students is suitable for use as teaching material in elementary schools.